Antibacterial activity of Gorgonian-associated actinomycetes against diabetic foot pathogens - DEVI OKTAVIA ANJANI; ESTER CHRISTIANA CHINTA LOSUNG; AGUS SABDONO; SRI SEJATI (Society for Indonesian Biodiversity, 2025)
Abstract. Anjani DO, Losung ECC, Sabdono A, Sedjati S. 2025. Antibacterial activity of Gorgonian-associated actinomycetes against diabetic foot pathogens. Biodiversitas 26: 4157-4166. Diabetic foot infection is a condition affecting the lower extremities that occurs in at least 15% of all diabetes patients. The treatment of diabetic foot infection has become increasingly challenging due to the risk of infection by microorganisms around the wound. The presence of antibiotic-resistant pathogenic bacteria further aggravates this condition. Therefore, the discovery of new sources of antibiotics is urgently needed. The aim of this study was to explore the antibacterial activity of actinomycetes, particularly those associated with marine gorgonians, to better understand their potential in the treatment of diabetic foot infection. Gorgonian samples were collected from Karimunjawa Waters, Indonesia. Antibacterial activity was screened using agar plug method against Escherichia coli, Staphylococcus aureus, Enterococcus sp., and Proteus sp.. The selected isolates were then identified through Gram staining and molecular identification. The NRPS, PKS-I, and PKS-II genes were detected through the PCR method. The results showed that 12 out of 45 isolates (26.7%) exhibited antibacterial activity against DFI pathogenic bacteria, with four isolates producing inhibition zone greater than 5 mm. The strongest antibacterial activity was exhibited by isolate UR.19.4 and EA.6.5.2 against S. aureus and E. coli with inhibition zones greater than 13 mm. Molecular identification revealed that UR.19.4 and EA.6.5.2 isolates had the closest similarity to Streptomyces griseobrunneus (99.76%) and Streptomyces zhaozhouensis (99.69%), respectively. The NRPS gene was detected in both S. griseobrunneus (UR.19.4 isolate) and S. zhaozhouensis (EA.6.5.2 isolate), while the PKS-II gene was detected only in S. griseobrunneus (UR.19.4 isolate). Therefore, these findings highlight the potential of actinomycetes isolated from Gorgonian as a promising antimicrobial source for treating diabetic foot infections.